Autoimmune Diseases in Children - Turdiyev Shukhrat Berdiyevich; Robbimova Bahora (Journal of Science in Medicine and Life, 2025)
Autoimmune diseases in children represent a group of chronic conditions that develop as a result of the immune system's misdirected attack on the body's own tissues. Although these pathologies are relatively rare in the pediatric population, they are of significant concern due to their severe progression and potential for long-term complications. The most common autoimmune diseases in children include Type 1 Diabetes Mellitus, Juvenile Idiopathic Arthritis, Celiac Disease, Autoimmune Hepatitis, and Systemic Lupus Erythematosus. Additionally, there are forms that affect the neuromuscular system, such as Guillain-Barré Syndrome, Dermatomyositis, and Myasthenia Gravis